Female sex as an independent prognostic factor in the development of oral mucositis during autologous peripheral stem cell transplantation - Gebri Enikő; Kiss Attila; Tóth Ferenc; Hortobágyi Tibor (2020)
Oral mucositis (OM) is a frequent complication of stem cell transplantation-associated toxicity in haematological malignancies, contributing to mortality. Therapy still remains mainly supportive. We assessed risk factors in retrospective analysis of 192 autologous peripheral stem cell transplantation patients with lymphoma and multiple myeloma (MM), respectively. Futhermore, we examined the hormone levels both in serum and saliva during transplantation in 7 postmenopausal female patients with lymphoma compared to healthy controls using electrochemiluminescence immunoassay (ECLIA). Multivariable analysis revealed neutrophil engraftment (p?
Keywords: Klinikai orvostan